Interaction of Plasminogen Activators and Plasminogen with Heparin: Effect of Ionic Strength - Rijken, Dingeman C; de Munk, Gerard A W; Jie, Annie F H (Thrombosis and Haemostasis, 1993)
In order to define the possible effects of heparin on the fibrinolytic system under physiological conditions, we studied the interactions of this drug with plasminogen and its activators at various ionic strengths. As reported in recent literature, heparin stimulated the activation of Lys-plasminogen by high molecular weight (HMW) and low molecular weight (LMW) two-chain urokinase-type plasminogen activator (u-PA) and two-chain tissue-type plasminogen activator (t-PA) 10- to 17-fold. Our results showed, however, that this stimulation only occurred at low ionic strength and was negligible at a physiological salt concentration. Direct binding studies were performed using heparin-agarose column chromatography. The interaction between heparin and Lys-plasminogen appeared to be salt sensitive, which explains at least in part why heparin did not stimulate plasminogen activation at 0.15 M NaCl. The binding of u-PA and t-PA to heparinagarose was less salt sensitive. Results were consistent with heparin binding sites on both LMW u-PA and the amino-terminal part of HMW u-PA. Single-chain t-PA bound more avidly than two-chain t-PA. The interactions between heparin and plasminogen activators can occur under physiological conditions and may modulate the fibrinolytic system.